1991
DOI: 10.1029/91jd00972
|View full text |Cite
|
Sign up to set email alerts
|

The Earth's radiation budget and its relation to atmospheric hydrology: 2. Observations of cloud effects

Abstract: This paper describes an observational study of the relationship between the cloudy sky components of the Earth's radiation budget (ERB) and space/time coincident observations of the sea surface temperature, microwave‐derived cloud liquid water and cloud cover. The study uses two ERB data sets; Nimbus 7 narrow field‐of‐view, broadband scanning radiometer data from June 1979 to May 1980 and the Earth Radiation Budget Experiment broadband scanning data from March 1985 to February 1986. Cloud fluxes are derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
90
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(90 citation statements)
references
References 34 publications
0
90
0
Order By: Relevance
“…[3] Despite the use of these products in a broad range of studies, from climate model validation to cloud-radiation interaction [e.g., Stephens and Greenwald, 1991;Zuidema and Hartmann, 1995;Chen and Roeckner, 1997;Borg and Bennartz, 2007;Ming et al, 2007], little is known regarding their error characteristics. Direct comparisons against in situ and surface-based microwave observations have yielded promising results for limited cases [Greenwald et al, 1993;Cober et al, 1996;Prigent et al, 1997;Offiler et al, 1998]; however, aircraft measurements have sample size and representativeness issues, as well as being relatively rare and costly; whereas observations from surface-based microwave radiometers can exhibit significant systematic errors [Turner et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…[3] Despite the use of these products in a broad range of studies, from climate model validation to cloud-radiation interaction [e.g., Stephens and Greenwald, 1991;Zuidema and Hartmann, 1995;Chen and Roeckner, 1997;Borg and Bennartz, 2007;Ming et al, 2007], little is known regarding their error characteristics. Direct comparisons against in situ and surface-based microwave observations have yielded promising results for limited cases [Greenwald et al, 1993;Cober et al, 1996;Prigent et al, 1997;Offiler et al, 1998]; however, aircraft measurements have sample size and representativeness issues, as well as being relatively rare and costly; whereas observations from surface-based microwave radiometers can exhibit significant systematic errors [Turner et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…The Earth Radiation Budget Experiment (ERBE) was the first satellite experiment that provided observational estimates of changes in the longwave and shortwave radiative fluxes at the top of the atmosphere due to clouds (Ramanathan et al, 1989;Harrison et al, 1990;Kiehl andRamanathan, 1990, Stephens andGreenwald, 1991;Hartmann et al, 1992 and others). The ERBE data revealed that changes in the shortwave and longwave fluxes due to the presence of deep clouds over the tropics were nearly of the same magnitude but opposite in sign (Kiehl and Ramanathan, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Although this mechanism no doubt plays a role in spreading water vapor beyond the immediate confines of convective towers, its importance in the large scale subsiding regions is uncertain, given the weak rainfall (Spencer, 1993) and rarity of deep convection there as witnessed by the lack of high clouds (e.g. Stephens and Greenwald 1991). An alternate hypothesis is that lateral mixing by large scale advection from regions directly moistened by deep convection provides the required source (e.g.…”
Section: Introductionmentioning
confidence: 99%